La crianza respetuosa en el desarrollo de la inteligencia emocional de los niños de preparatoria de la Unidad Educativa Amelia Gallegos Díaz, ciudad Riobamba - Manzano Montesdeoca, Madeline Anahi (2026)
This study examines respectful parenting, emphasizing respect, empathy, and emotional understanding as fundamental principles in children's development. Such an approach fosters an emotionally secure environment grounded in strong values. The findings indicate that children who receive guidance through active listening, well- defined boundaries, and unconditional affection are better equipped to regulate their emotions and manage frustration effectively. Conversely, the absence of appropriate parenting practices is associated with greater difficulty in expressing emotions constructively. Data collected through parental surveys corroborate the observed behavioral and emotional patterns in children. Therefore, it is imperative to implement strategies that promote effective parenting practices in the home, encouraging emotional expression, respectful support, and, most importantly, attentive, non-judgmental listening that validates children's thoughts and feelings.